2017
DOI: 10.3889/oamjms.2017.025
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Injuries in Fatal Motorcycle Accidents Seen in Lagos State University Teaching Hospital: An Autopsy-Based Study

Abstract: BACKGROUND:Deaths from motorcycle accident injuries have remained a major public health issue in Nigeria over the years.AIM:The study is to determine the age and gender distribution of the victims and to identify the cause of death and the anatomical pattern of injuries seen.METHODOLOGY:This is a 5-year autopsy-based study of all motorcycle accident deaths seen in Lagos State University Teaching Hospital between December 2009 and November 2014. The data were retrieved from autopsy reports, hospital case notes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
26
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 13 publications
11
26
3
Order By: Relevance
“…This is similar to other studies where the majority of patients involved in motorcycle crash were aged between 20 and 29 years [10]. In contrary one study done in Lagos Nigeria reported the majority of motorcycle crash injury victims to be the age of 31 - 40 years [11]. The reason why the youth are involved in commercial motorcycle could be explained by the fact that at this age group majority are engaged in productive activities predisposing to risks of being involved in road traffic crashes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is similar to other studies where the majority of patients involved in motorcycle crash were aged between 20 and 29 years [10]. In contrary one study done in Lagos Nigeria reported the majority of motorcycle crash injury victims to be the age of 31 - 40 years [11]. The reason why the youth are involved in commercial motorcycle could be explained by the fact that at this age group majority are engaged in productive activities predisposing to risks of being involved in road traffic crashes.…”
Section: Discussionsupporting
confidence: 87%
“…Among the road user category, motorcycle riders comprised (49%), followed by the passengers (35%) and then the pedestrians (16%). Similar observation was made in Lagos Nigeria where they looked at the patterns of injuries in fatal motorcycle crashes [11]. The increased likelihood of motorcycle occupants to sustain injuries in the event of a crash is because there is no protection over the inherently unstable motorcycle.…”
Section: Discussionmentioning
confidence: 60%
“…Underrepresentation of motorcycle crash data in the Tauma Registry is possibly an upshot of riders' efforts to avoid formal medical assessment and potential legal citation, which could lead to vehicle confiscation [38, 42]. A greater likelihood than reported of TSI for motorcycle, tricycle, or bicycle riders involved in crashes is possible, due to the increased vulnerability both of the rider's head/neck (related to limited helmet use [43-45]) and of the back [46].…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] The study[ 2 ] supports the existing evidence that the most of victims were young males in their productive age group and sustained a fatal head injury in road traffic accidents and only few of them reached the hospital in golden hour (in the present study, only 8% met the same). [ 3 4 5 6 7 ] It is interesting to note that all these patients were alive at the time of presentation to the hospital but sustained fatal injuries in varying severity and combinations. [ 2 ]…”
mentioning
confidence: 99%
“…[ 2 ] Another concern is that 50% of the victims had injuries to the chest, abdomen, and long bones[ 2 ] which are known to worsen the outcome in these patients. [ 3 5 6 8 ]…”
mentioning
confidence: 99%